Corneal crosslinking and intracorneal ring segments for keratoconus: A randomized study of concurrent versus sequential surgery. Issue 6 (June 2019) - Hersh, Peter S.; Issa, Reda; Greenstein, Steven A.
Abstract : Purpose : To assess outcomes of corneal crosslinking (CXL) and intracorneal ring segments (ICRS) (Intacs) used adjunctively, and then compare the safety and efficacy of concurrent versus sequential surgery. Setting : Cornea and refractive surgery subspecialty practice. Design : Prospective randomized clinical trial. Methods : Patients were randomized to one of two groups: ICRS first, immediately followed by CXL during the same session (n = 104), or ICRS followed by CXL 3 months later (n = 94). Outcomes included changes in maximum keratometry (K) and topographic inferior–superior (I–S) difference, maximum flattening of topographic K, and changes in uncorrected (UDVA) and corrected (CDVA) distance visual acuities. These were analyzed in the entire cohort, in the two randomized groups, and in subgroups stratified to ICRS size and placement. Patients were followed for 6 months. Results : The study comprised 198 eyes of 198 patients. Overall, maximum K decreased by an average of 2.5 D, I–S difference improved by 3.9 D, and there was an average maximum flattening of −7.5 D. The UDVA improved by 2.0 logarithm of the minimum angle of resolution lines, on average, and the CDVA improved by 1.1 lines. There was no significant difference between the sequential and concurrent groups in any of the outcomes analyzed. There were 6 clinically significant adverse events. Conclusions : CXL and ICRS can be used adjunctively with substantial improvement in corneal topography, and with no increase in safety concerns over each procedure alone. Sequential and concurrent treatment with ICRS and CXL show equivalent outcomes. Both thicker segment size and single segment placement seem to result in greater topographic improvement.